Pendampingan Model Desa Digital di Desa Marikangen - Hadi Kusmanto; Saluky Saluky (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2023)
Villages around the world are increasingly facing challenges in bringing information and communication technology (ICT) innovations into government and community services. This research discusses efforts to develop the Digital Village model implemented in Marikangen Village as an example of a case study. This research explores various aspects related to digital transformation at the village level, including technological infrastructure, community digital literacy, government policies, and socio-economic impacts. This research integrates community surveys, interviews with stakeholders, and data analysis to evaluate the Digital Village model implemented in Marikangen Village. The research results show increased public access to public services through digital platforms, such as e-government, e-commerce and online education. In addition, it was found that there was increased collaboration between village government, the private sector and the community in accelerating village development. In this context, this research also highlights the challenges faced, such as data security, privacy, and inequality in ICT access. The Digital Village Model implemented in Marikangen Village offers valuable insight into how villages can utilize the potential of ICT to improve the quality of life of their communities. This research contributes to further understanding of the importance of digital transformation at the village level and provides guidance for other villages wishing to develop similar models. In conclusion, the development of Digital Villages has great potential to overcome development challenges at the village level and create more connected and empowered communities.